LINGUISTIC PECULIARITIES OF ENGLISH AS A LINGUA FRANCA - Rahmonova , Gulhayo Xalilovna (Innovative Development in Educational Activities, 2022)
English as a lingua franca expresses a medium communication between speakers who can share neither their native or national language. ELF does not always occur among non-native speakers but also among interlocutors for whom English is first or second in academic conferences or meetings of the United Nations in New York. The article indicates the linguistic processes which are formed blending two or more languages’ features. Interference varieties were mostly appeared in Africa and Asia and brought the contexts colored with multilingual and multicultural features. These varieties have special characteristics in linguistic levels such as pronunciation, grammar, lexis and discourse. The results showed that the use of certain features in ELF which is regarded as ‘errors’ in Standard English are not considered as problematic and do not disturb communicative success.